Hubungan Pola Asuh Makan dengan Status Gizi Anak Usia Pra-Sekolah di Kelurahan Oesapa Kota Kupang - Julian Massardi Mira Mangngi; Marselinus Laga Nur; Mega O. Liufeto (Yayasan Literasi Sains Indonesia, 2025)
The nutritional status of toddlers can directly be affected by their dietary and health care patterns. The parenting pattern of parents specifically to toddlers needs to be done in earnest to achieve optimal child nutrition status. If the parenting pattern given to the mother to the child is good then the nutritional status of the child will be good too. Based on the Oesapa Health Center report in 2021-2022, the number of malnourished toddlers was 110 and in May 2024 there were 54 malnourished toddlers, 186 undernourished, 1,067 normal nutrition, 47 risk of overnutrition, 12 overnourished and 6 obesity. This study aims to determine the relationship of dietary parenting to the nutritional status of pre-school children in Oesapa Village, Kupang City. This type of research uses quantitative research with a cross sectional research design. The sampling technique in this study used Cluster sampling technique consisting of 79 samples of preschool children. Data analysis was performed using the Sperman Rank statistical test. The results showed a relationship between democratic parenting and nutritional status (0.338) has a moderate relationship, as well as the relationship between authoritarian parenting and nutritional status has a moderate relationship (0.314). However, there is no significant relationship between permissive parenting and nutritional status (0.011) which shows a very weak relationship. Parents are expected to be able to apply democratic parenting to children, especially in pre-school age children because good parenting can have an impact on children's nutritional status.